The Nigerian Chronicle – July, 1911 - Johnson, Chris (Editor) (Nigerian Chronicle Office, Kumolu House, Shitta Street, Lagos, Southern Nigeria., 1911)
A weekly review of progress in politics, economics, commerce, and general news, especially as affecting the Nigerians.
Keywords: Newspaper; Legislative Council Proceedings; Nigeria